Research on the selection of a preservative for a soft dosage form with a water-soluble protein-polysaccharide complex of the fungus pleurotus ostreatus - O. А. Kolpakova; N. V. Kucherenko (The State Expert Center of the Ministry of Health of Ukraine, 2021)
One of the important aspects in the development of new drugs is their standardization and comprehensive assessment of quality indicators, which guarantees safety and stability throughout the life cycle of the drug. Soft drugs for external use with components of natural origin usually require the introduction of preservatives to ensure microbiological stability. Therefore, research on the selection of preservative is a necessary phase in pharmaceutical composition preparation. Purpose - foundation of the type choice and concentration of an effective preservative (or their combination) for the introduction into the composition of the ointment of anti-scarring activity with a water-soluble protein-polysaccharide complex of the fungus Pleurotus ostreatus. The object of the study was an original ointment composition based on an emulsion, the active component of which is a water-soluble protein-polysaccharide complex of the fungus Pleurotus ostreatus. To increase microbiological stability, preservatives were added to the samples, which are most common in soft dosage forms (nipagin:nipazol, triclosan, bronopol and benzoic acid). Determination of the sensitivity of ointment samples to microorganisms was performed by the method of diffusion into agar («well method»), as a microbiological model used a common set of test strains of reference cultures of gram-positive and gram-negative bacteria and fungi. The study found that sample 7 had demonstrated high antimicrobial properties, where the diameters of the growth retardation zones were 34-35 mm to Staphylococcus aureus ATCC 25923, Basillus subtilis ATCC 6633, 29-31 mm for Escherichia coli ATCC 25922, Proteus vulgaris ATCC 4636 and Pseudomonas aeruginosa ATCC 27853. Growth retardation zones were 27-28 mm to fungi Candida albicans ATCC 653/885. Bronopol was introduced into the sample, this preservative should provide the necessary microbiological purity and stability of the prepared ointment. Studies show that soft dosage forms with substances of natural origin require the administration of antimicrobial agents. It has been experimentally proven that 0.2% bronopol provides effective microbiological stability of the soft dosage form with anti-scarring activity of water-soluble protein-polysaccharide complex of the fungus Pleurotus ostreatus.